2014
DOI: 10.3233/jad-140150
|View full text |Cite
|
Sign up to set email alerts
|

The ASCOMALVA (Association between the Cholinesterase Inhibitor Donepezil and the Cholinergic Precursor Choline Alphoscerate in Alzheimer's Disease) Trial: Interim Results after Two Years of Treatment

Abstract: Cholinesterase inhibitors (ChE-Is) are used for symptomatic treatment of mild-to-moderate Alzheimer's disease (AD), but long-term effects of these compounds are mild and not always obvious. Preclinical studies have shown that combination of ChE-Is and the cholinergic precursor choline alphoscerate increases brain acetylcholine levels more effectively than single compounds alone. ASCOMALVA (Effect of association between a ChE-I and choline alphoscerate on cognitive deficits in AD associated with cerebrovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 21 publications
0
34
0
5
Order By: Relevance
“…For clarity, the main characteristics of the ASCO-MALVA study are detailed below. Further details are reported in previous studies of our group [34][35][36]. Patients, diagnosed according to NINCDS-ADRDA criteria, were all in a mild/moderate-stage, showed brain ischemic lesions (in CT or MRI), and had at least two vascular risk factors (such as hypertension, diabetes, obesity, ischemic heart disease, hypercholesterolemia, hyperhomocysteinemia, smoking, previous cerebrovascular events, or family history of cardio-cerebrovascular diseases).…”
Section: Patients and Study Typementioning
confidence: 99%
See 2 more Smart Citations
“…For clarity, the main characteristics of the ASCO-MALVA study are detailed below. Further details are reported in previous studies of our group [34][35][36]. Patients, diagnosed according to NINCDS-ADRDA criteria, were all in a mild/moderate-stage, showed brain ischemic lesions (in CT or MRI), and had at least two vascular risk factors (such as hypertension, diabetes, obesity, ischemic heart disease, hypercholesterolemia, hyperhomocysteinemia, smoking, previous cerebrovascular events, or family history of cardio-cerebrovascular diseases).…”
Section: Patients and Study Typementioning
confidence: 99%
“…Two matched groups were analyzed: one (group A) treated with donepezil 10 mg/day plus choline alphoscerate 1,200 mg/day (associative therapy), the other (group B) with donepezil 10 mg/day + placebo (mono therapy). 175 subjects out of the originally planned 210 were recruited and 29 dropped out (12 in the donepezil only group, and 17 in the associative therapy group) for different causes, indicated in [34][35][36].…”
Section: Patients and Study Typementioning
confidence: 99%
See 1 more Smart Citation
“…One core pathway that impinges on the pathophysiology of epilepsy is that of acetylcholine biosynthesis and neurotransmission, which has only recently been investigated in the field of epilepsy research [ 5 , 7 ]. Since cholinergic decline is known to be involved in the pathogenesis of Alzheimer’s disease and cognitive dysfunction after trauma or cerebrovascular attack, both acetylcholinesterase inhibitors and acetylcholine precursors are being readily used in the aforementioned fields [ 21 - 25 ]. Therefore, the use of choline precursors in Alzheimer’s disease requires special attention if the patients also have epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylcholine precursors such as choline alfoscerate (α-GPC) and cytidine 5’-diphosphocholine (CDP-Choline) are important intermediates in the synthesis of both acetylcholine and cell membrane phospholipids. The ability of acetylcholine precursors to reduce or prevent neuronal insult has been tested both in clinical and animal studies in the field of stroke and Alzheimer’s disease [ 21 , 23 , 26 , 27 ]. Clinical studies have demonstrated that cholinergic precursors improved from cognitive impairment in Alzheimer’s disease and vascular dementia [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%